1003 Non-Medical Use of Prescription Stimulants for Daytime Sleepiness in University Students. (27th April 2018) - Willcott Benoit, W; King, E; Garland, S N
Abstract: Introduction: University students may use off-label prescription stimulants to prolong alertness or manage the daytime effects of poor sleep. Stimulant use has been associated with sleep disturbance, anxiety, increased heart rate, nausea, and dependence. The objective of this study was to determine the prevalence of, and factors associated with, non-medical use of prescription stimulants among university students. Methods: We surveyed 3, 699 university students aged 18–35 attending Memorial University in Newfoundland, Canada. Participants indicated whether or not they had used prescription stimulants (e.g., Adderall) for the specific non-medical purpose of helping them stay awake in the past month. Univariate and multivariate logistic regression were used to examine the demographic and clinical factors associated with stimulant use. Covariates included sociodemographics and the following standardized measures: Hospital Anxiety and Depression Scale, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, and Prescription Drug Attitudes Questionnaire. Results: Of the participants, 73% were female, with 49% aged between 18–21 years. One hundred eleven (3%) students reported the non-medical use of prescription stimulants to help them stay awake. Male sex (p=.02), poor sleep quality (p<.001), higher anxiety (p=.001), more depressive symptoms (p<.001), daytime sleepiness (p=.04), and permissive attitudes towards drug use (p<.001) were all independent predictors of non-medical use of prescription stimulants; however, when entered into a multivariate model the only clinical factors that remained significant were poor sleep quality (AOR=5.82; 95%Cl, 1.36 to 24.84; p=0.017) and more positive attitudes to non-medical use of prescription medication (AOR=2.52; 95%Cl, 1.06 to 5.99; p=0.037; AOR=10.41; 95%Cl, 4.57 to 23.72; p<0.001). Conclusion: The prevalence of stimulant use in this sample was lower than previously reported in other university samples. Those with poor sleep quality and/or more positive attitudes towards the non-medical use of prescription medication were more likely to use stimulants to reduce daytime sleepiness. Prevention or intervention programs should target beliefs that support stimulant taking behavior. Support (If Any): N/A.